Development of LaTeX Book Template for Submitting Assignments to Support Paperless Movement - Saefan*, Joko; Rini, Nur Widya; Marianti, Aditya; Rahayuningsih, Margareta (Universitas Syiah Kuala, 2024)
Paperless movement is a conservation effort. This refers to transitioning from conventional paper-based processes to replacing them with digital alternatives. The paperless movement has been globally implemented in various sectors, ranging from the corporate world to the educational sector. This movement is still little applied as a student's monumental work. This research aims to develop a book template using LaTeX for submitting assignments in the Computational Physics course. This template is designed to support the paperless movement as a conservation effort. We designed and developed a platform based on available LaTeX templates and then adapted it to the needs of computational physics courses. Instructions for using this template were also created and disseminated in learning classes. Next, we apply this template as a medium for collecting assignments and don't forget to ask students for responses regarding the use of this template. The outcome of the research is a book template that has already been used in the class. The students were very enthusiastic about learning the LaTeX program and they have been using it for document writing, especially related to mathematical equations. We hope that the development of this book template that we have carried out can become one of the conservation efforts in learning classes.